Gestión de control de inventarios en el depósito de madera los mellizos de la ciudad de Babahoyo. - Saltos Hinojosa, Evelyn Viviana (2022)
The investigation was carried out within the company called Los Mellizos Wood Deposit, the same one that is located within the City of Babahoyo. This business is dedicated exclusively to the purchase and sale of construction products, specifically cane and wood to make other structures such as floors, walls, doors, etc. The main objective of the research was to study the management that the Los Mellizos Wood Deposit carries out in relation to inventory control. Among the main results obtained, it was possible to show that the company does not have an administrative management process and therefore does not have an inventory management system, which has directly impacted its financial structure, generating that during these more than 30 years of existence has not been developed internally. This research is based on what is established by the Commerce Career of the Faculty of Administration, Finance and Information Technology, for which the line of research was applied: Financial Management, administrative, tax, audit, control. In the same way, since it is a private company that is analyzed, the research subline is involved: Companies and public and private institutions.